Targeted Cancer Therapy: Correlative Light‐Electron Microscopy Shows RGD‐Targeted ZnO Nanoparticles Dissolve in the Intracellular Environment of Triple Negative Breast Cancer Cells and Cause Apoptosis with Intratumor Heterogeneity (Adv. Healthcare Mater. 11/2016). Issue 11 (8th June 2016) - Othman, Basmah A.; Greenwood, Christina; Abuelela, Ayman F.; Bharath, Anil A.; Chen, Shu; Theodorou, Ioannis; Douglas, Trevor; Uchida, Maskai; Ryan, Mary; Merzaban, Jasmeen S.; Porter, Alexandra E.
Abstract : On page 1310 J. S. Merzaban, A. E. Porter, and co‐workers present fluorescently labeled RGD‐targeted ZnO nanoparticles (NPs; green) for the targeted delivery of cytotoxic ZnO to integrin αvβ3 receptors expressed on triple negative breast cancer cells. Correlative light‐electron microscopy shows that NPs dissolve into ionic Zn 2+ (blue) upon uptake and cause apoptosis (red) with intra‐tumor heterogeneity, thereby providing a possible strategy for targeted breast cancer therapy. Cover design by Ivan Gromicho.